2022
DOI: 10.1002/ps.7213
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of CYP304A1 associated with haedoxan A detoxification in Aedes albopictus by RNAi and transgenic drosophila

Abstract: BACKGROUND: Insect cytochrome P450 monooxygenases play important roles in the detoxification metabolism of endogenous and exogenous compounds. Haedoxan A (HA) from Phryma leptostachya L. is a highly efficient natural pesticide used to control houseflies and mosquitos. CYP4C21 and CYP304A1 were previously demonstrated to be transcriptionally increased in Aedes albopictus in response to HA exposure, but their involvement in HA metabolism is unknown. RESULTS: Our data showed that CYP304A1 expression levels in A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…melanogaster carrying PxGSTs1 demonstrated a higher LC 50 to all tested insecticides, compared to the nontransgenic control strains (w1118) (Table ). In previous reports, transferring CYP304A1 from Aedes albopictus to fruit flies found that the fruit flies’ resistance to haedoxan A increased by 2.051-fold . Transferring Cyp6 cm1 of B.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…melanogaster carrying PxGSTs1 demonstrated a higher LC 50 to all tested insecticides, compared to the nontransgenic control strains (w1118) (Table ). In previous reports, transferring CYP304A1 from Aedes albopictus to fruit flies found that the fruit flies’ resistance to haedoxan A increased by 2.051-fold . Transferring Cyp6 cm1 of B.…”
Section: Resultsmentioning
confidence: 96%
“…In previous reports, transferring CYP304A1 from Aedes albopictus to fruit flies found that the fruit flies' resistance to haedoxan A increased by 2.051-fold. 41 Transferring Cyp6 cm1 of B. tabaci to D. melanogaster conferred 2-to 3-fold resistance to neonicotinoid insecticides. 42 These studies all indicated that the increased resistance level after transferring the detoxification enzyme gene confirmed the metabolic function of the detoxification enzyme.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An indication of its function is provided by a recent study on Ae . albopictus larvae suggesting that it is induced by haedoxan A and participates in haedoxan A detoxification [ 61 ]. Further studies are needed to elucidate mechanisms of gene regulation for the cytochrome P450 system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect of exogenous substances on insect reproduction and development, the detoxification and metabolism of exogenous substances by pests have been extensively studied [ 28 , 29 , 30 , 31 ]. In this study, 28 DEGs were primarily enriched in the “drug metabolism- other enzymes”, “glutathione metabolism” and “Metabolism of xenobiotics by cytochrome P450” pathways.…”
Section: Discussionmentioning
confidence: 99%